Frequency of Eyelid Lesions in Patients Presenting at Ophthalmology Department of a Tertiary Care Hospital - Mohammad Parvez, Shahid Anwar Bhatti, Faisal Nawaz, Muhammad Waseem, Abdul Munim, Naseer Ahmad (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Approximately 5 percent of all skin cancers are eyelid tumors, which is also among the most prevalent location for head and neck neoplastic diseases. If diagnosed too late, malignant eyelid tumors necessitate more extensive surgery. Objective: The aim of this study was to find out the Eyelid Lesions Frequency in patients presenting at Ophthalmology Department of a Tertiary Care Hospital Methodology: The current study was conducted at the department of ophthalmology Ophthalmology Muhammad college of Medicine Peshawar from February 2022 to December 2022 after taking permission from the ethical board of the hospital. Overall 154 individuals who had surgery for eyelid abnormalities at the ophthalmology were included. Participants with eyelid lesions that may or may not be spreading to other tissues were enrolled in the research. Age, gender, lesion type, lesion location, histopathology assessment, therapy, and follow-up were among the details provided. Data was entered was Microsoft Excel sheet and present in tables in the form of frequency and percentage. Results: A total of 154 individuals of both genders and different aged groups with lesions on their eyelids were examined in this study. There were 77 benign tumors and a similar amount of malignant ones. The most often diagnosed malignant lesion on the lid was carcinoma of squamous cells 46 (59.7%). Older men, farmers, and laborers with a history of prolonged sun exposure constituted the majority of those affected. It was followed by a benign lesion called epidermal inclusion cyst 26 (33.76%). Malignant lesions were seen in individuals older than 50, but benign lesions were found among individuals younger than 30. Of the 154 lesions, 26 (16.88%) had exenteration and 128 (83.11%) had excision biopsy. A biopsy was done on all 77 (100%) of them. Each of the 77 (100%) benign and 52 (67.5%) malignant lesions had a biopsy. Exenteration was done on 25 (32.4%) of the malignant tumors. Conclusion: Our study concluded that squamous cell carcinoma and epidermal inclusion cyst are the most common eyelid lesions among individuals presenting to ophthalmology department. Keywords: Frequency; Eyelid Lesions: malignant tumors